Century of research on property cycles: a literature review - Jadevicius, Arvydas; Sloan, Brian; Brown, Andrew (International Journal of Strategic Property Management, 2017)
The existence of cycles in building and property, has grown to have significant importance in the UK and internationally; whereas property markets have been characterised by boom and bust cycles with a negative impact on the national economies. As a result, property cycles became a popular research topic amongst property professionals and scholars, with a greater understanding of the cyclical behaviour of the property market being seen as a major guide to the financial success (failure) of property investments. consequently, considerable literature has accumulated over the years on the subject. This paper provides a review of this literature, mostly written in the UK and US, with international insights on the subject. This paper reviews research on the subject chronologically over a one hundred-year period. The study is designed to provide readers with a historical overview of Property cycles research by emphasising the underlying theme which dominated a particular period of this research, as well as indicating methods, data analysis techniques employed and outcomes of these studies. Its ai is to put more clarity on the subject, as well as help to navigate anyone interested in Property cycles through a considerable amount of research which has accumulated over the last century.